Slow Budget Realization: An Empirical Analysis in Higher Education - Zulfaturrohmah, Festi; Handoko, Fitrian Budi; Abiprayu, Kris Brantas (Management Analysis Journal, 2021)
This research aims to test the influence of planning, human resources, and organizational commitment to budget absorption at the Faculty of Education UNNES. One indicator of achieving the effectiveness and efficiency of budget management is the distribution of budget absorption evenly in each period. In the end, the implementation of an effective and efficient performance-based budget has not been fully implemented. There is still a delay in the absorption of funds, especially in some faculties at Universitas Negeri Semarang. This study aims to test a wide range of factors that can cause delays in budget absorption. The result show that budget realization affected by several factors such as budget planning, human resource and organizational commitment